Associations between the pre‐pregnancy body mass index and gestational weight gain with pregnancy outcomes in Japanese women. Issue 5 (21st April 2014) - Tanaka, Tomohito; Ashihara, Keisuke; Nakamura, Michihiko; Kanda, Takayoshi; Fujita, Daisuke; Yamashita, Yoshiki; Terai, Yoshito; Kamegai, Hideki; Ohmichi, Masahide
Abstract Aim To examine the associations between the pre‐pregnancy body mass index (BMI) and gestational weight gain (GWG) with pregnancy outcomes in Japanese women. Methods The medical records of 1883 Japanese women who delivered singleton infants from January 2010 to January 2013 at Osaka‐Minami Medical Center were retrospectively reviewed. We use the BMI classification which the World Health Organization defined for Asian populations and the GWG classified based on the current 2009 Institute of Medicine (IOM) recommendations. The odds ratio (OR) of each of the groups for the different pregnancy outcomes were compared to the recommended group using a logistic regression analysis adjusted by age, gestational weeks, parity, weight gain, mode of delivery, pregnancy induced hypertension (PIH) and gestational diabetes mellitus. Results Women who were obese (BMI, ≥25 kg/m2) and overweight (BMI, 23–24.9 kg/m2) had a higher rate of developing PIH (adjusted OR, 6.68 and 3.21 [95% confidence interval [CI], 3.31–13.3 and 1.29–7.24]). In contrast, GWG exhibited a correlation with the weight of the infant. The inadequate GWG group had a higher rate of small‐for‐gestational age (SGA) infants (adjusted OR, 1.72 [95% CI, 1.22–2.46]). The rate of emergency cesarean section was not significantly different between the groups. Conclusion A pre‐pregnancy BMI less than 23 kg/m2 is desirable to prevent Japanese women from developing PIH. GWG within the IOM recommendations also reduced the risk of PIH and SGA.